1999
DOI: 10.1046/j.1439-0396.1999.00218.x
|View full text |Cite
|
Sign up to set email alerts
|

Re‐examination of the metabolizable energy contents of various rations containing different types and levels of bacterially fermentable substrates in digestibility experiments with growing pigs

Abstract: Introduction  Feedstuffs with elevated contents of bacterially fermentable substrates (BFS: GFE 1987) offered to pigs have intermediate metabolizable energy (ME) contents compared with feedstuffs mainly composed of starch or hardly fermentable fibre (H adorn et al. 1996a,b). Consequently, BFS‐elevated feeds could be used as major components enabling pig fattening rations to obtain the ME values required for feed calculation from tabulated values (DLG 1991) or equations based on nutrient composition (GFE 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
12
1
2

Year Published

2002
2002
2015
2015

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 6 publications
6
12
1
2
Order By: Relevance
“…The supplementation of SBP resulted in less digestibility of nonfiber and greater digestibility of fiber fractions, thus confirming the results of several other experiments where SBP was fed to pigs (Chabeauti et al, 1991;Kreuzer et al, 1999;Bindelle et al, 2009). A considerable proportion of SBP fiber is degraded in the small intestine of pigs, whereas the ileal digestibility of ash, protein, and fat was reduced at increased SBP intake (Graham et al, 1986;Dierick et al, 1989).…”
supporting
confidence: 84%
See 1 more Smart Citation
“…The supplementation of SBP resulted in less digestibility of nonfiber and greater digestibility of fiber fractions, thus confirming the results of several other experiments where SBP was fed to pigs (Chabeauti et al, 1991;Kreuzer et al, 1999;Bindelle et al, 2009). A considerable proportion of SBP fiber is degraded in the small intestine of pigs, whereas the ileal digestibility of ash, protein, and fat was reduced at increased SBP intake (Graham et al, 1986;Dierick et al, 1989).…”
supporting
confidence: 84%
“…However, the absolute amount of BEDN increased with SBP as compared with the basal diet-fed pigs, indicating an elevated bacterial N fixation in the hindgut. The greater UDN excretion observed in SBP-fed pigs may have resulted from increased quantity of fiber-bound N, and the increased WSN excretions can be explained by the enhanced endogenous secretion of enzymes, reduced urea absorption at the end of the ileum, increased resecretion of urea through the hindgut wall, or lysis of bacteria before excretion (Kreuzer et al, 1999).…”
mentioning
confidence: 99%
“…Consequently, differences in supply of soluble fibre among diets were great and led to a significant increase of DM and N intake. However, when citrus and beet pulp were added to diets with similar NDF levels, little effect of inclusion of soluble fibre on daily BEDN excretion was also reported (Kreuzer et al, 1999; experiment 1). In the same way, several works (Graham et al, 1986;Bach Knudsen et al, 1993;Glitso et al, 1998) have demonstrated that a significant proportion of the dietary soluble fibre (from 0.20 to 0.40) is fermented before the ileum, and so it would not be a direct substrate for hindgut microbial population.…”
Section: Discussionmentioning
confidence: 97%
“…However, in the current study, BEDN proportion in total faecal N tended to be lower when a higher proportion of highly fermentable fibre was given in OP diets. Previous works (Kreuzer et al, 1999;Heimendahl et al, 2010) measured faecal N fractions in pigs using the same methodology than in the current study. In these studies, a significant decrease of BEDN proportion in total faecal N was observed with soluble fibre supplementation, but daily faecal N and BEDN excretion increased, because highly fermentable sources of fibre (as citrus or sugar beet pulp) replaced starch in the experimental feeds, so that dietary NDF content increased in parallel to by-products inclusion.…”
Section: Discussionmentioning
confidence: 99%
“…In the same way, there is a general agreement in that inclusion of fermentable fibre, as sugar beet pulp or inuline, leads to a shift in the N excretion from faeces to urine (Aarnink & Verstegen, 2007), which is generally associated to an enhanced metabolic urea retention and excretion as microbial protein in the faeces (Kreuzer et al, 1999). This shift would imply in turn a decrease of ammonia emissions from the slurry with fibre supplementation but also a higher fermentation activity and methane losses, as observed by Montalvo et al (2013).…”
Section: Effects Of Dietary N Concentrationmentioning
confidence: 94%